Development and engineering application validation of alkali-activated full-component shield tunnel spoil regenerated solid-waste grouting material - Zhiran Yang; Yu Zhou; Li Wang; Shizhuo Zou; Jinfei Chai; Yufei Fang; Shichao Jiang; Hui Ma (Journal of Materials Research and Technology)
To address the issues of high disposal costs and low resource recovery efficiency of shield tunnel spoil (STS), this study proposes an Alkali-Activated Full-Component Shield Tunnel Spoil Regenerated Solid-Waste Grouting Material (AFS-RSWGM). Cement, fly ash, shield-sieved sand, and soil were used as raw materials, combined with synergistic alkali activation and the pozzolanic effect of fly ash. Key parameters, including water-binder ratio (A), binder-sand ratio (B), and shield tunnel spoil soil (STSS)-water ratio (C), were optimized using Response Surface Methodology (RSM). Rheological and mechanical tests assessed construction adaptability and structural stability, while Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and hydration heat analyses clarified alkali activation mechanisms. Alkali activation enhanced silico-aluminate dissolution in STSS, forming amorphous gels and ettringite (AFt). The fly ash pozzolanic effect released reactive SiO2 and Al2O3 continuously, refining the interfacial transition zone and reducing porosity. Optimal mix ratios (A = 1.091, B = 0.819, C = 0.197) significantly improved compressive strength over conventional cement systems. Rheological analyses revealed reduced yield stress and enhanced shear-thinning behavior. Hydration heat demonstrated bimodal exothermic characteristics, confirming effective aluminosilicate activation and polymerization. Applied in Jinan Metro Line 4, AFS-RSWGM fully reutilized STS, achieving better ground settlement control without segment leakage. This low-cement-content approach combined with solid waste recycling technology provides a practical solution for green construction, carbon reduction, and resource recycling in underground engineering.